Design and Development of a Display Board Using Wireless and Bluetooth Concepts - Adithya T.G.,; Praveen N.,; Suhasini V.K.,; K.N. Vijaykumar,; Akash R.,; Maya Srinivas,; Venugopal Rao S.,; Sanjan Kashyap,; Pavithra G.,; Sindhu Sree M.,; T.C.Manjunath, (Journal of Electronic Design Engineering, 2022)
The wireless notice board design employing Bluetooth technology is the subject of the research discussed in this paper. This project uses Bluetooth technology to synchronize a wireless electronic display board to convey the message to the public in a novel and ultimately intriguing way. This would enable us to communicate virtually instantly and without delay by sending an SMS or voice message, which is superior to the outdated conventional method of posting the message on a noticeboard. The proposed technology can be utilized in malls, large buildings, colleges, and other public spaces to improve security, raise awareness of emergencies, and reduce risks. Messages can be sent to the Bluetooth module via the GSM module and shown on the LCD board using the Bluetooth module. The information on the LCD Display is displayed on the wireless electronic notice board without the use of any wires. It uses less energy and is very simple to use. The wireless notice board's portable circuit can be moved around. The work given here is a mini-project completed by electronics and communication engineering students in the second semester at Dayananda Sagar College of Engineering in Bangalore, Karnataka.